The Odyssey from Symptom to Diagnosis of Pulmonary Hypertension from the Patients and Spouses Perspective - Bodil Ivarsson; Anders Johansson; Barbro Kjellström (SAGE Publishing, 2021)
Introduction/objective: Diagnostic delays in pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) are related to increased morbidity and mortality. The risk of a delayed, or even a missed, diagnosis is high as the conditions are rare. The aim was to describe patients' and spouses' experiences of the journey from the first symptom to an established diagnosis. Methods: A secondary analysis of 31 transcripts, based on 2 primary datasets containing interviews with 17 patients and 14 spouses, was carried out and analyzed according to qualitative content analysis. Results: One overarching category was revealed from the content analysis; "The journey from doubt and hope to receive the diagnosis. " Five subcategories were identified as: overall experiences; ignoring symptoms; seeking primary care/hospital specialty care; blame and stigma; and finding a pulmonary hypertension specialist clinic. The main finding was that both patients and spouses experienced that waiting for a diagnosis and the deteriorating state of health led to anxiety and frustration. The knowledge about rare diseases among health professionals needs to be improved to enable a timelier diagnosis and initiation of treatment. Conclusion: Patients' and spouses' lives were negatively affected by having to search for a correct diagnosis. In order for health care to identify rare diseases earlier, a well-functioning and responsive health care system, in primary care as well as in specialist care, is needed. Symptoms like breathlessness and fatigue are often unspecific but should not be ignored. Keeping the patient and spouse in the loop, and providing information that the search for an answer might take time is essential for health care providers to create trust.